Diseño de un modelo de planeación de inventarios en una empresa distribuidora de GLP (Gas licuado del petróleo) que permita un adecuado control (2022)
The present research work arises from the need to improve the current inventory model of the Liquefied Petroleum Gas - LPG distribution company, in it there is an inefficiency in said management for the consumption of its products; This has caused an accumulation of low-rotation products and shortages in high-rotation products, therefore, when analyzing the behavior of demand and cylinders per item, it was possible to identify the main problems in the inventory area, which allowed determining a adequate forecast simulation model for each item, analyzing the pattern presented by its demand, where the processes were optimized by reducing the times in it, all this under a statistical analysis approach developed by the researchers